Emergence of Apiotrichum mycotoxinivorans Invasive Infection in Thailand: Report of The First Four Cases in Southeast Asia - Prof Methee Chayakulkeeree; Dr. Piriyaporn Chongtrakool (International Journal of Infectious Diseases)
Back ground: Apiotrichum mycotoxinivorans (previously known as Trichosporon mycotoxinivorans) is a rare fungal pathogen that cause invasive pulmonary infection, especially in those with cystic fibrosis. We report here the first 4 cases in Southeast Asia of non-pulmonary invasive infection caused by A. mycotoxinivorans. Case Description: The first case was a 46-year-old man with diabetes mellitus and end stage renal disease (ESRD) on regular hemodialysis, admitted with severe COVID-19 pneumonia. He developed respiratory failure required intubation. He was treated with remdesivir. He received broad spectrum antibiotics to treat superimposed bacterial pneumonia. One week later, he developed fever and blood cultures grew A. mycotoxinivorans with amphotericin B minimal inhibitory concentration (MIC) of 2 µg/mL and voriconazole MIC of 0.5 µg/mL. Voriconazole was commenced. He succumbed 2 weeks after treatment. The second case was a 73-year-old woman with ESRD, presented with fever, chills and hypotension after hemodialysis. Peripheral blood cultures grew Stenotrophomonas maltophilia. However, blood cultures from both lumens and the tip of the Permcath grew both S. maltophilia and A. mycotoxinivorans with amphotericin B MIC of 2 µg/mL and voriconazole MIC of 0.12 µg/mL. She was treated with levofloxacin and voriconazole but she expired 9 days later. The third case was a 77-year-old man with ESRD, presented with fever and chills during hemodialysis 2 weeks prior to admission. Blood cultures from the Percath and peripheral vein grew S. maltophilia. Five days later, the blood culture from the Percath's venous site was reported additional growth of A. mycotoxinivorans with amphotericin B MIC of 0.5 µg/mL and voriconazole MIC of 0.12 µg/mL. Voriconazole was commenced and the Permcath was removed. He was discharged after 5 days of hospitalization. The fourth case was a 58-year-old woman with cholangiocarcinoma of distal bile duct, presented with hematemesis 3 months after Whipple procedure. Abdominal computed tomography showed intra-abdominal abscesses. She underwent repaired pancreaticojejunostomy with abdominal toilet. Ascites fluid culture grew A. mycotoxinivorans. She was referred to another hospital for treatment. Discussion: Extrapulmonary A. mycotoxinivorans infection is extremely rare. We report here 3 cases of extrapulmonary blood stream and a case of intra-abdominal infection. The 3 cases of blood stream infection were related to dialysis catheter. Interestingly, 2 of those were co-infected with S. maltophilia. The organisms had low MIC to voriconazole, but most of them had high amphotericin B MIC. Therefore, voriconazole should be the appropriate treatment of invasive A. mycotoxinivorans infection. Combination with antibacterial agents may be considered as co-infection with bacteria is common. The morality rate is high, approximately 50% of cases. Conclusion: A. mycotoxinivorans invasive infection is emerging and can cause non-pulmonary catheter-related blood stream infection, resulting in high mortality. Fungal species identification and antifungal susceptibility testing are important for choosing appropriate antifungal therapy.